Gas Teddy Bear Bobo - Arnar Þór Úlfarsson 1980-; Björn Heiðar Rúnarsson 1990-; Bjarki Dagsson 1982- (2013)
Heildartexti lokaskýrslu. Prentað eintak og öll fylgiskjöl á CD eru varðveitt á bókasafni HR This report details a final project in Reykjavik University school of Computer Science conducted in the fall of 2013. The goal of this project was to create a mobile web application named Gas Teddy Bear Bobo, often referred to as Bobo. Bobo is a mobile application which allows users to see real time gas prices, offers that the gas companies have active and the user’s fuel consumption. Additionally, Bobo lists and shows gas stations in Iceland as well as providing driving route to individual stations with respect to users position. Detailed overview of the web services Bobo connects to, the methodology used in designing and implementing the application and how the project progressed through the 15 weeks of the project. Finally it gives the results of the simplicity tests and ideas on future development of the application. Entrio ehf.